Fabrication of highly porous and adhesive thick Y2O3 film by room-temperature spray process for thermal insulation coating. Issue 10 (15th May 2023) - Yun, Sae-Jung; Kim, Jung-Hwan; Jang, Jongmoon; Cha, Hyun-Ae; Ahn, Cheol-Woo; Yoon, Woon-Ha; Choi, Jong-Jin; Hahn, Byung-Dong
Abstract: An effective strategy for manufacturing ceramic thick films with high porosity and robustness was proposed by aerosol deposition (AD). The agglomeration of the Y2 O3 and polyethylene powder composites was investigated to prepare porous films. After exploring a suitable particle distribution, Y2 O3 and polyethylene composite powder were prepared using two different mixing methods with various polyethylene contents. During the transportation in vacuum, easily separated mixture powders of Y2 O3 and polyethylene caused insufficient energy result in partially delaminated films. In contrast, the appropriate agglomeration of the Y2 O3 –polyethylene composite powders can be crushed with higher kinetic energy by increased mass, resulting in uniform and robust porous films with high adhesive strength. After burning, the Y2 O3 –polyethylene (8 wt% polyethylene) thick film (∼100 μm) exhibited high porosity (66%), low thermal conductivity (∼0.15 W/m·K at room temperature), and good adhesion strength (8.4 MPa). In this study, we provide effective guidelines for fabricating AD-based porous ceramic films deposited at room temperature with low thermal conductivity and high adhesive strength.